Response of four indigenous cattle breeds to natural tsetse and trypanosomosis challenge in the Ghibe valley of Ethiopia - Lemecha, H.; Mulatu, W.; Hussein, I.; Rege, J.E.O.; Tekle, T.; Abdicho, S.; Ayalew, W. (Elsevier, 2006)
A comparative study on the response of four indigenous cattle breeds of Ethiopia, namely Abigar, Horro, Sheko and Gurage, to natural challenge of trypanosomosis in the Tolley–Gullele area of the Ghibe valley has been undertaken from August 2000 until August 2004. Fifty female yearlings each of Horro, Sheko and Abigar and 31 of the Gurage were purchased from their natural habitats and introduced in to medium to high tsetse–trypanosomosis challenge area of the Ghibe valley. While the natural habitats of first three breeds are naturally infested with tsetse flies and trypanosomosis, that of the Gurage is known to be very minimal, if any, and hence the Gurage breed was used in this study as the known susceptible breed. During the study animal health, production performance and tsetse fly situation were monitored monthly. The Sheko breed has manifested very significantly (p < 0.001) high overall average packed cell volume (PCV) values (25%) compared to that of Abigar (24%), Horro (23%) and Gurage (22%). It also had the lowest mean trypanosome prevalence rate of 9% against 23% of Horro, 26% of Abigar and 27% of Gurage, and the least number of Berenil® treatments (1.36) compared to Abigar (4.0), Horro (4.6) and Gurage (6.7). While the Abigar manifested high sensitivity and frequent death to PCV depression, the Horro showed strong resilience to PCV depression and better response to Berenil® treatment assistance. At this stage the Sheko breed was also found to be equal to the other breeds in its reproductive performance. These results need to be substantiated with further in-depth investigation including immune response, animal behavior and environmental influences.